An mpox quadrivalent mRNA vaccine elicits sustained and protective immunity in mice against lethal vaccinia virus challenge - Entao Li; Qiyuan Yang; Wenyu Xie; Qizan Gong; Xiaoping Guo; Jinge Zhou; Jiachen Zhang; Xia Chuai; Yucai Wang; Sandra Chiu (Emerging Microbes and Infections)
Assessing the long-term efficacy of MPXV vaccine candidates is crucial for the global response to the ongoing mpox epidemic. Built upon our previous study of the mpox quadrivalent mRNA vaccine, herein we reported that MPXV-1103 could elicit sustained humoral and cellular immunity in mice, including the induction of MPXV A35/B6/A29/M1-specific IgG antibodies, VACV neutralizing antibodies and activated cytotoxic CD8+T cells, which provides 100% protection against lethal VACV challenge even at 280 days after the first vaccination. Our results provide critical insights for orthopoxvirus vaccine development.